Thermal Hyperalgesia After Sciatic Nerve Block in Rat Is Transient and Clinically Insignificant. Issue 2 (1st March 2013) - Janda, Allison; Lydic, Ralph; Welch, Kathleen B.; Brummett, Chad M.
Abstract : Abstract: Ropivacaine has been associated with transient heat hyperalgesia in sciatic nerve blocks in rat. The goal of the present study was to evaluate the hypothesized presence of transient heat hyperalgesia after perineural injection of ropivacaine with a secondary subanalysis of 2 published studies. Paw withdrawal latency was used to assess the duration of sensory blockade and presence of heat hyperalgesia at 210, 240, 270, and 300 minutes and 24 hours after injection. The analysis revealed hyperalgesia at a single time point (240 minutes after injection; mean difference, −0.60 seconds; P = 0.012) that resolved within 30 minutes, and there was no other significant hyperalgesia at other time points. Although statistically significant, the single time point measurement represented only an 11% change from baseline and was no longer present 30 minutes later. These data support the need for a reevaluation of the interpretation that pain can be worsened by perineural ropivacaine injection.